2020
DOI: 10.1063/5.0012471
|View full text |Cite
|
Sign up to set email alerts
|

Flow dynamics of a fluidic oscillator with internal geometry variations

Abstract: An experimental study is conducted to examine the impact of internal geometry of a fluidic oscillator on its working mechanisms, i.e., the widths of the inlet wedge W1, mixing chamber W2, and exit throat W3, normalized by the width of the inlet throat W0. Using time-resolved particle image velocimetry, the flow dynamics both inside and outside the oscillator are measured simultaneously. The phase-averaged flow fields are obtained using proper orthogonal decomposition analysis based on which the pressure fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…For this design, the distance between two opposing Coanda surfaces is curtailed substantially. Wen et al (2020) reported that by reducing the distance between the mixing chamber walls, the size of the recirculation bubble reduces, resulting in a lower jet spreading, similar to our case. We can reasonably conclude that the different Coanda surfaces modify the dynamics of the flow separation and recirculation, and thus the properties of the periodic symmetry breaking of the flow inside the mixing chamber.…”
Section: Flow Regimes Of the Modified Geometriessupporting
confidence: 87%
“…For this design, the distance between two opposing Coanda surfaces is curtailed substantially. Wen et al (2020) reported that by reducing the distance between the mixing chamber walls, the size of the recirculation bubble reduces, resulting in a lower jet spreading, similar to our case. We can reasonably conclude that the different Coanda surfaces modify the dynamics of the flow separation and recirculation, and thus the properties of the periodic symmetry breaking of the flow inside the mixing chamber.…”
Section: Flow Regimes Of the Modified Geometriessupporting
confidence: 87%
“…This confirms that each oscillator comprises two identical parts. From the time-averaged velocity field, it can be observed that the main jet in the mixing chamber shows no apparent movement, resulting in a jet flow very similar to a stationary jet (Wen et al , 2020). The figures also show that the fluid-jet power of the fluidic oscillator is greater than that of the SJ.…”
Section: Results and Interpretationsmentioning
confidence: 99%
“…Below this high velocity zone, two localized regions with relatively higher velocities (orange) branch out in a direction parallel to each side of the exit nozzle. They are associated with the double peak velocity profile typically exhibited by a sweeping jet (Aram et al, 2018;Wen et al, 2018;Wen et al, 2020).…”
Section: Sweeping Jet At the Quiescent Flow Conditionmentioning
confidence: 93%